Sorcery and Gold - Kerven, Rosalind (Cambridge University Press, 1998)
Ingrid and Kjartan live in the troubled Viking Age: danger is everywhere and no stranger can be trusted. So what should they do when a foreigner comes knocking at their door, begging for help? The law-makers are hunting him down as an evil criminal, but he insists he is innocent. As they struggle to discover the truth, the two children are swept up into a terrifying adventure, and a desperate race against time...
Keywords: Adventure; Juvenile Fiction